Effect of alkali activator and granulated blast furnace slag on the properties of lithium slag-based high-strength lightweight aggregates - Yingda Zhang; Zhaopeng Tang; Xianliang Zhou; Yantao Zheng; Zihao Liu (Scientific Reports)
Abstract This study investigated the effects of NaOH molarity (6–14 M) and ground granulated blast furnace slag (GBFS) content (0–45%) on the properties of lithium slag (LS)-based cold-bonded lightweight aggregates. Bulk density, water absorption, porosity, and cylinder compressive strength were evaluated, and microstructural characterization was conducted using SEM, XRD, FTIR, MIP, and TG/DTG. Results showed that increasing NaOH molarity and GBFS content reduced water absorption (from 15.87 to 5.88%) and porosity (from 34.79 to 13.39%), while enhancing bulk density (731–1074 kg/m³) and compressive strength. At 30% GBFS, the 28-day strength increased by 224.48%, from 3.35 MPa (M6-30) to 10.87 MPa (M14-30). At 12 M NaOH, raising GBFS content from 0 to 45% increased strength by 435.62%, from 2.33 MPa to 12.48 MPa. LS without GBFS achieved 2.33 MPa, indicating inherent pozzolanic activity. Microstructural analysis revealed that performance improvement was due to enhanced geopolymerization and reduced harmful pores (> 200 nm). The M8-30 mix (915.68 kg/m³, 5.98 MPa) showed potential for meeting high-strength lightweight aggregate criteria with mix optimization. These findings demonstrate the feasibility of valorizing LS into high-performance lightweight aggregates, contributing to waste utilization and low-carbon construction.